(untitled) (LEARNing Landscapes, 2015)
University-school partnerships can offer teachers a space for inquiry into theory-based practice related to teaching for equity, inclusivity, and justice. The Teachers College Inclusive Classrooms Project (TCICP) invites city teachers to join an Inquiry to Action Team where they collectively interrogate students’ access to full participation in schools. Teachers are enthusiastic about this work and eagerly share their wisdom and carefully document their yearlong journeys into creating greater access and participation for students. The inquiry teams function as an alternate space for educators to share their work, ponder their pedagogical beliefs, and analyze power relationships in their classrooms and schools. As participants are validated in their work in this alternate space, they are able to build agency as intellectuals and act inclusively and for social justice within their own school spaces.